THE EFFECT OF PRICES, PRODUCT REVIEWS, EASE OF USE, AND SECURITY OF TRANSACTIONS ON PURCHASING DECISIONS ONLINE IN SHOPEE - Homami Rahayu; Adi Sismanto; Tezar Arianto (BIMA Journal (Business, Management, & Accounting Journal), 2020)
This study aims to determine the effect of prices, product reviews, ease of use, and security of transactions on purchasing decisions online at Shopee (case study of Economics Faculty students at Muhammadiyah University, Bengkulu). This study uses a sample of 105 respondents using purposive sampling technique. Data collection techniques using observation and questionnaires. The analysis technique used is the regression of respondents' responses, multiple linear regression, correlation coefficient analysis and coefficient of determination (R2). This research uses validity test, reliability test, and classic assumption test followed by hypothesis testing. Based on the results of multiple linear regression analysis, the results of the research have an effect on the online purchasing decisions at Shopee It is proven by the results of the t test showing tcount t2/2 (2.022 0.1982) and (sig α = 0.046 0.050), this means that H0 is rejected and Ha is accepted. Product reviews have a positive and significant effect partially on online purchasing decisions at Shopee, this is evidenced by the results of the t test which shows the value of tcount t2/2 (2.212 0.1982) and (sig α = 0.029 0.050), this means H0 is rejected and Ha is accepted the ease of use partially has a positive and significant effect on online purchasing decisions at Shopee, this is evidenced by the results of the t test which shows the value of tcount  t2/2 (2.113 0.1982) and (sig α = 0.037 0.050), this means H0 is rejected and Ha is accepted. Security Transactions have a positive and significant effect partially on online purchasing decisions at Shopee, this is evidenced by the results of the t test which shows the value of tcount t2/2 (2.955 0.1982) and (sig α = 0.004 0.050), this means H0 is rejected and Ha is accepted. Price (X¬1) Product Review (X2), Ease of Use (X3) and Transaction Security (X4) jointly influence the Purchase Decision (Y) online at Shopee, this is evidenced by the F test showing the value of tcount ttable, namely (6,392 2.69) and (sig α = 0,000 0.05) this means that H0 is rejected and Ha is accepted.